A Cross-sectional Study on Netizen Tabayyun Practices in Receiving and Conveying Information on Social Media - Rosmawati Mohamad Rasit; Mohamad Zulkifli Abd Ghani; Muhamad Faisal Ashaari; Md Rozalafri Johori (USIM PRESS, 2024)
VOL. 34 NO. 2 (2022)